Inferior vena cava diameter and vascular calcification jointly influenced cardiovascular outcomes among patients with end-stage kidney disease - Chia-Ter Chao; Min-Tser Liao; Chung-Kuan Wu (BMC Cardiovascular Disorders)
Abstract Introduction Excess body fluid, a prevalent complication in patients with end-stage kidney disease (ESKD), correlates with adverse outcomes. Whether higher vascular resistance, in the form of vascular calcification (VC), modulates the negative outcome influences posed by excess fluid remains unclear. We aimed to determine whether combination of inferior vena cava (IVCD) and VC, in the form of aortic arch calcification (AoAC) severity, influences the risk of adverse outcomes in ESKD patients. Methods We retrospectively analyzed enrolled chronic hemodialysis patients from a single center, dividing them according to IVCD and VC severity. After comparing their baseline clinical features, we analyzed the combined influences of IVCD and VC on ESKD patients’ risk of major adverse cardiovascular events (MACEs), cardiovascular and all-cause mortality over follow-up. Results Totally 227 ESKD patients were assigned to the non-to-mild VC/low IVCD (30.0%), non-to-mild VC/high IVCD (28.6%), mod-to-severe VC/low IVCD (23.3%), and mod-to-severe VC/high IVCD (18.1%) groups, respectively. After nearly 4 years follow-up, we showed the risk of MACEs was the highest among those with mod-to-severe VC and high IVCD (hazard ratio [HR]5.45,95% confidence interval [CI]2.33–12.75), followed by non-to-mild VC and high IVCD (HR 4.39,95% CI 1.93-10.00), and those with mod-to-severe VC and low IVCD (HR 3.91,95% CI 1.64–9.33), accounting for demographic, morbidities, laboratory, and medication variables. Similar trend was found on the risk of cardiovascular and all-cause mortality. Conclusions Fluid status and vascular resistance in the form of IVCD and VC additively worsened the cardiovascular outcome among ESKD patients. Cardiovascular care for ESKD patients should ideally encompass volume management and VC amelioration.